A literature review [2000–2022] on vehicle acoustics: Investigations on perceptual parameters of interior soundscapes in electrified vehicles - Münder, Mara; Carbon, Claus-Christian (Frontiers in Mechanical Engineering, 2022)
The interior soundscape of a vehicle is an essential asset for experienced comfort and feedback of a car’s driver, especially in the premium automotive industry. Here we offer a literature review on the perception of acoustic characteristics of electrified vehicles (EVs) and the impressions and associations they convey to the individual — the driver, the customer, the user. The reduction of the overall sound pressure level (SPL) in EVs offers the opportunity to create exceptional quiet interior soundscapes. At the same time, the reduced SPL challenges NVH (Noise, Vibration, and Harshness) engineers to reduce remaining noises that are no longer masked by operational combustion while creating vehicle-adequate acoustics with pleasingly comfort-assets and operational feedback of the current driving mode. The analyzed body of literature covers research from the 21st century (2000-2022). We aim to comprise the current state of research highlighting specific achievements already made. Furthermore, we show evident gaps that need to be filled and considered in future research.